2008
DOI: 10.1159/000184717
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variation and mosaicism

Abstract: Mosaicism is the presence of cells within an organism that have a different genetic composition despite deriving from a single zygote. The consequence of this depends on the number and type of cells that are affected as well as the specific DNA involved. There are several diseases where mosaicism is known to occur, but the currently observed frequency is presumably an underestimation due to the difficulty of detecting changes in only a percentage of cells. Recent advances in technology have provided a greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 98 publications
1
37
0
2
Order By: Relevance
“…Side-by-side comparison these two cases 83350 (father) and 83349 (daughter) showed identical breakpoint regions and the expected differences between the hemizygous and mosaic state (Figure 2). Similar mosaic genomic changes somatic or somatic and germline mosaicism have been reported in Duchenne Muscular Dystrophy, Neurofibromatosis 1 and 2 and other skin, blood and neuromuscular disorders, reviewed by Notini et al and Erickson (Erickson, 2010;Notini et al, 2008). For the first time, we showed that the existence of mosaic mutations (large deletions) may play a significant role in the development of MO in patients who are negative for mutations in Exostosins when analyzed by sequencing and MLPA.…”
Section: Discussionsupporting
confidence: 84%
“…Side-by-side comparison these two cases 83350 (father) and 83349 (daughter) showed identical breakpoint regions and the expected differences between the hemizygous and mosaic state (Figure 2). Similar mosaic genomic changes somatic or somatic and germline mosaicism have been reported in Duchenne Muscular Dystrophy, Neurofibromatosis 1 and 2 and other skin, blood and neuromuscular disorders, reviewed by Notini et al and Erickson (Erickson, 2010;Notini et al, 2008). For the first time, we showed that the existence of mosaic mutations (large deletions) may play a significant role in the development of MO in patients who are negative for mutations in Exostosins when analyzed by sequencing and MLPA.…”
Section: Discussionsupporting
confidence: 84%
“…Application of nextgeneration sequencing methods will allow for an easier and more sensitive calling of the smallest mosaic aberrations in the near future and will add up to the (scarce) data generated recently on this topic by some other groups. [30][31][32][33] Various causes could account for the discrepancy in CNV findings between our congenital anomaly twin cohort and the Parkinson's cohort. First of all, an age factor: the rather high prevalence of mosaic CNVs in PD twins could have been generated during lifetime.…”
Section: Discussionmentioning
confidence: 78%
“…11 The clinical history of the mother included a relatively late menarche (16 years) with irregular menstruation up to the first pregnancy. Before this pregnancy she had received hormonal stimulation, but this was stopped before conception.…”
Section: Resultsmentioning
confidence: 99%